Outcomes of physical therapy in patients with chronic low back pain: Učinki ambulantne fizikalne terapije pri bolnikih s kronično bolečino v križu - Klemenc Ketiš, Zalika (Acta Medico-Biotechnica, 2022)
Purpose: To assess the outcomes of a10–treatment sessions program of physical therapy regarding the level of pain and health–related quality of life in patients with chronic, non–specific, low back pain. Methods: A consecutive sample of adults (N = 129) with chronic, non–specific, low back pain was assessed for improvement after a 10–day physical therapy program, consisting of an average of 3 different physical modalities, as prescribed by family physicians. A visual analog pain scale and EuroQol questionnaire (EQ–5D and EQ–VAS) were completed by patients before and after physical therapy. Results: The intensity of pain after 10 days of physical therapy was on average lower (1.7 ± 1.8 points; P < 0.001). The assessment of overall health on the EQ–VAS was on average better (10.3 ± 15.2 points; P < 0.001). The score of the EQ–5D was on average lower (0.8 ± 1.2 points; P < 0.001). The patients that were not on sick leave during the physical therapy reported a greater lowering of the intensity of pain than those on sick leave (P = 0.03). Patients with a BMI > 29 kg/m2 had a significantly higher change in the assessment of overall health on the EQ–VAS (P = 0.022). The patients that had group exercise in the set of procedures reported a greater improvement in overall health on the EQ–VAS compared to the patients that did not have group exercise (P = 0.036). The patients with anxiety and depression had a significantly higher change in the composite score of the EQ–5D (P = 0.013). Patients with a BMI > 29 kg/m2 had a significantly higher change in the composite score of the EQ–5D (P = 0.013). Conclusion: Physical therapy has some effect in the short–term treatment of patients with chronic, non–specific, low back pain, but the viability of such procedures in this population of patients is questionable.